Acupuncture as a Therapeutic Intervention for Alleviating Pain Associated with Knee Osteoarthritis in the Elderly - Suptika Strisanti, Ida Ayu; Ida Ayu Anom Rastiti; Kadek Buja Harditya; I Dewa Ayu Agra Darmawati; Komang Rosa Tri Anggaraeni (Babali Publisher, 2025)
Introduction: Osteoarthritis is a common joint disease associated with aging, with knee osteoarthritis (KOA) affecting both elderly men and women in Indonesia. KOA is a major cause of disability and immobility, significantly impacting the quality of life of the elderly. Acupuncture is frequently used as a complementary and alternative medicine therapy to alleviate pain associated with KOA. This study aims to investigate the effect of acupuncture in relieving KOA-related pain in the elderly. Method: A pre-experimental study with a one-group pre-post-test design was conducted, involving 30 elderly respondents from the Payangan Desa hamlet, selected using purposive sampling. Data were collected using an observation sheet and the Comparative Pain Scale to evaluate pain levels. All respondents provided informed consent before participating in the study. The Wilcoxon Signed Rank Test was used to analyze and interpret the results. Result: Before the intervention, 9 respondents (30.0%) reported moderate knee pain, 10 (33.3%) reported severe pain, and 9 (30.0%) reported very severe pain. After the intervention, pain levels decreased significantly: 4 respondents (13.3%) reported no pain, 14 (46.7%) experienced mild pain, and 12 (40.0%) had moderate pain. The change in pain levels was statistically significant (p < 0.05). The median pain score decreased from Md = 5.50 before the intervention to Md = 2.00 after, with a z-value of -4.53 and r = 0.58. Conclusion: Acupuncture therapy is effective in alleviating pain levels among elderly individuals suffering from KOA-related pain, with no observed negative side effects. Acupuncture is a promising, safe, and effective alternative medicine for elderly patients with KOA.